Development of an Inexpensive Spectrometer Tool with a Tracker to Investigate Light Spectrum - Prayogi, Soni; Silviana, Fitria; Saminan, Saminan (Jurnal Pendidikan MIPA, 2023)
One of the most fascinating areas of physics is likely optics. However, it also includes some of the phenomena that students find to be less clear-the light spectra produced by light diffraction. The experimental analysis of light spectra to evaluate radiation bodies typically requires specialized and expensive equipment that is typically out of the price range for schools. Few teachers are proficient in measuring the wavelengths of light in a spectrum. In this study, we describe a low-cost, straightforward setup that can measure light spectra accurately enough to be utilized in physics and chemistry lectures. We demonstrate how the shareware program Tracker, which is frequently used to teach mechanics, may be used to measure wavelengths with a resolution of roughly 2 nm. Several methods are also available for calibrating various setups, depending on the level of accuracy required.Keywords: optics, spectrum, experimental, wavelength.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp28-38